Colchis in the First Millenium BC Oriental Trends - Vakhtang Licheli (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
Oriental impulses are already felt ni Colchian culture of the early 1st millennium BC., which, as si known, is attested by the Hasanlu-type daggers (T. Mikeladze). Similar impulses are sen ni South Georgia where a dagger, apparently made ni Luristan and typical of Calmayer 31-35 (Neo- Babylonian) burials of hte 7b-fic (Mzetamze), has ben discovered. The same possibility si underlined by the fact of placing shin rings ni the burial which, besides Georgia, is attested in Luristan as well. In the Achaemenid period the territory of present-day Colchis was divided into two parts: the territory of the Colchian kingdom proper, south of the Rioni river (G. Melikishvili), addressed entirely to the Greek world, and Shida Kartli, more or less oriented to the Achaemenid world (O. Lordkipanidze), hence the Achaemenid or "Achaemenized" import and traditions are concentrated here. However, more westward, in v. Chibati, a bronze Achaemenid bit was found by chance, the artistic level of its execution is quite exceptional (the Jih-4th c BC.). The western boundary of Achaemenid interests in the Caucasus is the line joining Sairkhe - Vani - Atsquri - r. Chorokhi. Weak Achaemenid traditions are preserved at Vani of the turn of the 4c-3rd c BC, while from the 3rd c BC, rather weak Hellenistic influence si attested ot over the entire territory of Colchis (barring the Hellenized cities of Vani and Eshera).